1969
DOI: 10.4315/0022-2747-32.12.485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Time and Temperature on Salmonellae in Inoculated Butter1,2

Abstract: Three batches of butter made in Small experimental lots from commercial cream were contaminated with Salmonella, typhimurium var. copenhagen by inoculating the cream and wash water. Contaminated butter was held 10 weeks at 77, 40, 32, 0, and −10 F. Salmonella increased at 77 F and decreased at ≤ 40 F. Most significant decline in viable Salmonella was at 0 or −10 F, in unsalted butter followed in order by lightly salted butter and moderately salted butter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, there are several reports that demonstrate that pathogens are capable of growing in colloidal products. In a study by Sims and others (1970), butter readily supported the growth of Salmonella at 24 °C. Lanciotti and others (1992) reported that Listeria monocytogenes and Yersinia enterocolitica grew in light butter incubated at 4 and 20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are several reports that demonstrate that pathogens are capable of growing in colloidal products. In a study by Sims and others (1970), butter readily supported the growth of Salmonella at 24 °C. Lanciotti and others (1992) reported that Listeria monocytogenes and Yersinia enterocolitica grew in light butter incubated at 4 and 20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Turkish Codex butter should not be contaminated with Salmonellae and Staphyloccus aureus and these microorganisms should not be detected in 25 g of sample. Salmonella can grow in butter at 25 8C and could not be eliminated by refrigeration or freezing (Sims et al, 1970). Holliday et al (2003) reported that Salmonella and E. coli O157.H7 can grow on the surface of sweet cream whipped salted butter exposed to high relative humidity at 21 8C.…”
Section: Resultsmentioning
confidence: 99%